Efektifitas Supervisi Akademik untuk Meningkatkan Kemampuan Literasi Digital dalam Pengelolaan Pembelajaran - Ahmad Raiza Zulfikar; Aceng Muhtaram Mirfani; Cicih Sutarsih; Diding Nurdin (Universitas Pendidikan Indonesia, 2022)
The purpose of this research was to analyze the effect of the principals academic supervision to increase digital literacy on the teaching performance. The method used in this research is a descriptive method with a quantitative approach. This study took a sample of the population using a questionnaire instrument as a data collection technique. Schools that became the population and sample of 63 public elementary schools in Ciparay District. Sampling using a questionnaire which includes the location of the study in elementary school of Ciparay district with a total of 80 respondents. The results of this research explained that the principal's academic supervision effective to increase digital literacy the teacher on the management of teaching learning. The implication of the results of this study is that if the principal's academic supervision and digital literacy are carried out properly, it will have an impact on improving teacher learning management.